A Optimalisasi Keuntungan Produksi Keripik Talas TARA Menggunakan Linier Programming Dengan Metode Simpleks - Palahudin; Alisya Subhani; Alya Junieta Dwiyana; Giska Wafiq Azizah Setiawan; Nawa Julika; Siti Aidini Khoerunnisa (Universitas Muhammadiyah Metro, 2025)
Food business requires efficient resource management to achieve optimal production and maximum profit. This research aims to optimize the production combination at TARA Taro Chips Factory by utilizing simplex-based linear programming method. This method is used to maximize company profits through proper resource allocation. The research data was obtained through the literature method and processed using the Solver tool in Microsoft Excel to minimize calculation errors. The results show that the factory can achieve maximum profit of Rp446,970 per day through the optimal production combination. The simplex method proved to be effective in solving resource allocation problems and provided a strategic reference in decision making to improve efficiency and innovation in product development